Energy Loss Analysis of Dual Power Supply-Powered Motor Drive During Supercapacitor Energy Storage Discharge - Ģirts Staņa; Kaspars Kroičs (Energies)
Electrical energy consumers, such as AC motors, can be supplied by a dual power supply consisting of a DC grid and a supercapacitor (SC) energy storage system. The efficiency of energy flow can vary depending on where the energy storage system is connected to the DC network, due to the resistance associated with transmission. This paper details an analysis of energy loss in SC and DC source dual-supply systems based on mathematical and simulation models. This study considers three variants, where the SC is connected to a DC line and located close to the load, distant from the load, and close to the DC source. For each case, simulation and mathematical models are developed and the simulation results are verified. Through simulations, the influence of the supercapacitor’s discharge proportionality coefficients on power supply efficiency is also studied.